Modelo de gestión administrativa para el complejo turístico Tolas de Socapamba, cantón Ibarra - Martínez Trujillo, Diego Esteban (2023)
At present, tourism companies have made a qualitative leap in terms of the type of administration adopted. The Tolas de Socapamba Tourist Complex, located in the city of Ibarra, offers lodging, food and recreation services. The main problem identified is the empirical administration by the owners, which affects the quality of the services provided. The objective of this work is to design an administrative management model that adapts to the needs of the Tolas de Socapamba Tourist Complex to optimize business resources, through effective compliance with functions and processes. The methodology used is based on a basic investigation with a mixed approach. The instruments to collect the data were a questionnaire applied to 40 tourists from the complex, as well as an interview with the collaborators of the establishment. The most relevant results were summarized in a SWOT analysis, where one of the main strengths is the variety of services offered by the establishment including swimming pools, sports courts, event room, restaurant with typical food and lodging, which attracts different types of visitors. . Likewise, the weakness where work must be done properly is in the part of the commercialization of services\; there are not the marketing and advertising strategies that the business requires to reach a wider audience. On the other hand, there is an opportunity to establish alliances with other tourism companies, travel agencies or local institutions that can increase exposure and capture new market segments. The worst threat to the company is economic instability in the Ecuadorian territory. It is concluded that the implementation of the management model is considered as a process of continuous improvement, where periodic evaluations of performance and results obtained allow adjustments based on the findings.